2019
DOI: 10.1002/ajim.22952
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset asthma in non‐allergic women working in dampness damaged buildings: A retrospective cohort study

Abstract: Background There is still no consensus about the association between working in dampness‐damaged buildings and new onset of asthma among adults. The purpose of this study was to assess asthma in the staff of two psychiatric clinics where some premises were suffering from dampness. Methods A 20‐year retrospective cohort study was performed using questionnaires. Results Incidence rate ratios (IRR) for asthma were non‐significantly elevated (IRR = 2.3) among exposed individuals. The risk was greater among females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This may explain the different OR values observed for men and women in this work because there appear to be gender-based differences in immune responses 33–35. These differences are not well understood but similar effects have been seen for asthma 36 37…”
Section: Discussionmentioning
confidence: 70%
“…This may explain the different OR values observed for men and women in this work because there appear to be gender-based differences in immune responses 33–35. These differences are not well understood but similar effects have been seen for asthma 36 37…”
Section: Discussionmentioning
confidence: 70%
“…For exposure to cleaning agents, 7 studies were included for new‐onset asthma 54–59 and 8 for the impact on asthma‐related outcomes 31,60–66 (Tables 2.3 and 2.4). For damp/mould exposure, 26 studies were included for new‐onset asthma 67–92 and 22 studies for the impact on asthma‐related outcomes 93–114 (Tables 2.5 and 2.6). For pesticide exposure, 8 studies were included for new‐onset asthma 115–122 and 2 studies for the impact on asthma‐related outcomes 123,124 (Tables 2.7 and 2.8).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have previously observed that indoor MD exposure is associated with respiratory health effects such as upper respiratory tract symptoms, the development of asthma and asthma deterioration [ 1 , 2 , 3 ]. So far, these studies have mainly focused on children’s risk of asthma, other respiratory tract symptoms, and MD exposure at home or in schools [ 4 , 5 , 6 , 7 , 8 ], but some previous research has also established a temporal relationship between workplace MD exposure, asthma [ 9 , 10 , 11 , 12 ] and rhinitis symptoms [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%